The first Caipirasuchus (Mesoeucrocodylia, Notosuchia) from the Late Cretaceous of Minas Gerais, Brazil: New insights on sphagesaurid anatomy and taxonomy - Martinelli, Agustín Guillermo (2018)
Field work conducted by the staff of the Centro de Pesquisas Paleontológicas Llewellyn Ivor Price of the Universidade Federal do Triângulo Mineiro since 2009 at Campina Verde municipality (MG) have resulted in the discovery of a diverse vertebrate fauna from the Adamantina Formation (Bauru Basin). The baurusuchid Campinasuchus dinizi was described in 2011 from Fazenda Três Antas site and after that, preliminary descriptions of a partial crocodyliform egg, abelisaurid teeth, and fish remains have been done. Recently, the fossil sample has been considerably increased including the discovery of several, partially articulated fish remains referred to Lepisosteiformes and an almost complete and articulated skeleton referred to a new species of Caipirasuchus (Notosuchia, Sphagesauridae), which is the main subject of this contribution. At present, this genus was restricted to the Adamantina Formation cropping out in São Paulo state, with the species Caipirasuchus montealtensis, Caipirasuchus paulistanus, and Caipirasuchus stenognathus. The new material represents the holotype of a new species, Caipirasuchus mineirus n. sp., diferenciated from the previously ones due to the following traits: last two maxillary teeth located posterior to anterior edge of infraorbital fenestra, elongated lateroventral maxillo-jugal suture-about 1/2 the anteroposterior maxillar length-and contact between posterior crest of quadrate and posterior end of squamosal forming an almost 90° flaring roof of the squamosal, among others. C. mineirus was found in the same outcrop than Campinasuchus but stratigraphically the former occurs in the lower portion of the section with no unambiguous data supporting the coexistance of both taxa.